The Evolution of Chromosome Numbers: Mechanistic Models and Experimental Approaches - Mayrose, Itay; Lysak, Martin A (Genome biology and evolution, 2021)
Chromosome numbers have been widely used to describe the most fundamental genomic attribute of an organism or a lineage. Although providing strong phylogenetic signal, chromosome numbers vary remarkably among eukaryotes at all levels of taxonomic resolution. Changes in chromosome numbers regularly serve as indication of major genomic events, most notably polyploidy and dysploidy. Here, we review recent advancements in our ability to make inferences regarding historical events that led to alterations in the number of chromosomes of a lineage. We first describe the mechanistic processes underlying changes in chromosome numbers, focusing on structural chromosomal rearrangements. Then, we focus on experimental procedures, encompassing comparative cytogenomics and genomics approaches, and on computational methodologies that are based on explicit models of chromosome-number evolution. Together, these tools offer valuable predictions regarding historical events that have changed chromosome numbers and genome structures, as well as their phylogenetic and temporal placements.
Keywords: modely genetické; polyploidie; Genomics; Chromosomes, Plant; malování chromozomů; Models, Genetic; Polyploidy; Chromosome Painting; genom rostlinný; chromozomy rostlin; Evolution, Molecular; molekulární evoluce; Genome, Plant; genomika